Cu14 Cluster with Partial Cu(0) Character: Difference in Electronic Structure from Isostructural Silver Analog. Issue 18 (26th July 2019) - Li, Yan‐Ling; Wang, Jie; Luo, Peng; Ma, Xiao‐Hong; Dong, Xi‐Yan; Wang, Zhao‐Yang; Du, Chen‐Xia; Zang, Shuang‐Quan; Mak, Thomas C. W.
Abstract: An atom‐precise Cu 0 ‐containing copper cluster, Cu14 (C2 B10 H10 S2 )6 (CH3 CN)8 (abbreviated as Cu14 ‐8CH3 CN) is reported, which is synthesized via a simultaneous reduction strategy and fully characterized by single‐crystal X‐ray diffraction, ESI‐TOF‐MS, and X‐ray photoelectron spectroscopy. Cu14 ‐8CH3 CN is the only copper cluster that has a virtually identical silver structural analog, i.e., Ag14 (C2 B10 H10 S2 )6 (CH3 CN)8 (hereafter as Ag14 ‐8CH3 CN). Nevertheless, density functional theory calculations reveal that the electronic structure of Cu14 ‐8CH3 CN differs significantly from the superatom electronic configuration of Ag14 ‐8CH3 CN. Moreover, Cu14 ‐8CH3 CN shows room‐temperature luminescence and good electrocatalytic activities in the ethanol oxidation reaction and detection of H2 O2 . This pair of unprecedented analogous molecular nanoscale systems offer an ideal platform to investigate the fundamental differences between copper and silver in terms of catalytic activity and optical properties. Abstract : Atom‐precise Cu 0 ‐containing cluster Cu14 ‐8CH3 CN synthesized via a simultaneous reduction strategy is fully characterized by single‐crystal X‐ray diffraction, ESI‐TOF‐MS, and X‐ray photoelectron spectroscopy. Density functional theory calculations show that its electronic structure differs significantly from the superatom electronic configuration of the isostructural Ag14 analog. Moreover, Cu14 ‐8CH3 CN shows room‐temperature luminescence and good electrocatalytic activities in ethanol oxidation reaction and detection of H2 O2 .